Contextualization of Training Input in Multi-Level Replication and Scaling-up Approach in EFL Teacher-Training - Hazel Acosta; Diego Cajas; Elizabeth Minchala (Profile: Issues in Teachers' Professional Development)
This study deviates from the standard view of template-based training courses that have dominated the experience of in-service English teachers in Ecuador. Its purpose is to underscore the contextualization of training modules as a strategic method for duplicating and scaling up multi-level teacher training to sustain their knowledge and skills. The impact is assessed through a three-level survey administered to 394 teachers from three provinces. The results suggest that the influence of class size and the adaptability and replicability of training are factors that influence the effectiveness and sustainability of an English as a foreign language program. The study highlights the crucial role of collaboration that facilitates collective efforts to contextualize training to achieve profound insight related to classroom practices.